2017
DOI: 10.1109/tnano.2017.2691713
|View full text |Cite
|
Sign up to set email alerts
|

Crossbar-Based Memristive Logic-in-Memory Architecture

Abstract: Aquesta és una còpia de la versió draft d'un article publicat a IEEE transactions on nanotechnologyhttp://hdl.handle.net/2117/104473 Papandroulikadis, G., Vourkas, I., Abustelema, A., Sirakoulis, G., Rubio, A. Crossbar-based memristive logic-in-memory architecture. "IEEE transactions on nanotechnology", 1 Abril 2017, vol. 16, núm. 3, p. 491-501. DOI: 10.1109/TNANO.2017 © 2017 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…However, most such relevant works omit crucial factors such as variability (both cycle-to-cycle and device-to-device) and endurance of memristors; being the latter a major limitation to be considered if frequent switching is necessary during computations. For instance, recently Papandroulidakis et al [21] suggested using different T memristor technology for memory and computing tasks to address endurance issues. Likewise, another logic scheme called Scouting Logic [22] was proposed to alleviate the endurance requirement while executing logic operations by just sensing the memristor state, even though this scheme eventually suffers from device variability.…”
Section: Introductionmentioning
confidence: 99%
“…However, most such relevant works omit crucial factors such as variability (both cycle-to-cycle and device-to-device) and endurance of memristors; being the latter a major limitation to be considered if frequent switching is necessary during computations. For instance, recently Papandroulidakis et al [21] suggested using different T memristor technology for memory and computing tasks to address endurance issues. Likewise, another logic scheme called Scouting Logic [22] was proposed to alleviate the endurance requirement while executing logic operations by just sensing the memristor state, even though this scheme eventually suffers from device variability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, all memristive based logic/computational circuits, i.e. computation of Boolean functions in memristor-only circuits [49] as well as logic computation parallelism with memristors [48] would be examined as feasible promising in-memory computing nano-architectures. As an alternative novel analog computing concepts utilizing massively-parallel computing architectures, enabled by networks of memristors could be also equally considered [74].…”
Section: Computing Concretementioning
confidence: 99%
“…[10][11][12][13] Recent studies have identified various useful and efficient stateful gates for better computing efficiency, and as a result, stateful logic technology has advanced significantly. [14][15][16][17][18][19][20][21][22][23][24] Such various gates are possible by simultaneously applying designed operating voltages on the multiple cells. In general, the word lines of input cells and output cells are biased to a conditioning voltage (V COND ) and programming voltages (V PGM ), respectively.…”
Section: Introductionmentioning
confidence: 99%